Gen-Z Consumer Behavior: What Factors are Affecting Repurchase Intention of Online Ticket Reservation? - Mira Meilia Marka; Sufiana Noor (The Graduate School of Sahid University, 2023)
This study analyzes how to increase repurchase intention of online transportation ticket ordering platform. Respondents are Gen-Z who were born in 1996 – 2007. The research sample is 105 people. Primary data sourced from questionnaires serves as a data source. Data analysis used the SMARTPLS program. the results of this research states that the perception of benefits builds trust. Higher consumer trust will create purchase intention. There is no influence of Security toward Repurchase Intention. Consumer trust is formed from perceived usefulness and security felt by consumers. trust can mediate the relationship between perceived usefulness and repurchase intention as a partial mediation. The relationship between security and repurchase intention can be mediated by full trust (full mediation).